2019
DOI: 10.3390/antiox8090359
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Broccoli Sprout Powder in Gastro-Resistant Capsules Protects against the Acidic pH of the Stomach In Vitro but Does Not Increase Isothiocyanate Bioavailability In Vivo

Abstract: Broccoli sprout powder is a rich source of glucosinolates, which are hydrolysed to isothiocyanates in the presence of the enzyme myrosinase. We showed that in vitro incubation of broccoli sprout powder extract with isolated lymphocytes resulted in the upregulation of transcription factor Nrf2, however, there was no increase in Nrf2 protein levels in lymphocytes isolated 3 h following the ingestion of broccoli sprout powder by healthy volunteers. This highlights the general issue that potential health benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…One group of microcapsules were coated with an intestinal soluble polymer, Eudragit L 100-55, to investigate the effect of different solubility coatings on the viability of Lactobacillus plantarum. The Eudragit L100-55 coating degradation is pH-dependent, and dissolved above pH 5.5 [28,29]. By this enterosolvent coating, the liberation of bacteria in acidic medium was avoided [30].…”
Section: Discussionmentioning
confidence: 99%
“…One group of microcapsules were coated with an intestinal soluble polymer, Eudragit L 100-55, to investigate the effect of different solubility coatings on the viability of Lactobacillus plantarum. The Eudragit L100-55 coating degradation is pH-dependent, and dissolved above pH 5.5 [28,29]. By this enterosolvent coating, the liberation of bacteria in acidic medium was avoided [30].…”
Section: Discussionmentioning
confidence: 99%
“…Such constraints may be overwhelmed by using the multi-unit granule system (MUPS), since the small size of the granules would increase the interaction with the surface of the intestinal tract for drug absorption, thus allowing for a faster dissolution. Finally, the authors showed an upregulation of the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) in lymphocytes cultivated in vitro, but not in lymphocytes isolated 3 h after broccoli sprouts intake by the volunteers, which may be explained by the low concentration of ITC found in plasma (1 µM) [ 64 ].…”
Section: Dietary Interventions With Cruciferous Sproutsmentioning
confidence: 99%